Green supply chain management, agility, and resilience in Mexican manufacturing companies - Esponda Pérez, Jorge Alberto; Marroquín Figueroa, Julia María; Tapia de Aquino, Juan Manuel; Rocha Leyva, Francisco Javier (Revista Venezolana de Gerencia, 2026)
The objective of the work is to analyze how green supply chain management practices influence the environmental and financial performance of Mexican manufacturing firms, considering supply chain agility and resilience as key organizational capabilities for adaptation in dynamic environments. The methodology consisted of an empirical, quantitative, and cross-sectional study applied to 270 manufacturing companies in Mexico, using a structured questionnaire and Partial Least Squares Structural Equation Modeling (PLS-SEM) to test the proposed relationships among the constructs. The results show that green supply chain management practices have a positive and significant effect on both environmental and financial performance, while supply chain agility and resilience act as important mediating mechanisms that strengthen these relationships. Additionally, big data analytics enhances the impact of green practices on environmental performance, although its moderating effect on financial performance is not statistically significant. It is concluded that the integration of green supply chain management with dynamic capabilities such as agility, resilience, and data-driven decision-making enables manufacturing firms to respond more effectively to environmental pressures, improve sustainability outcomes, and maintain competitiveness within the Mexican industrial context.